Enhancing decision making processes in project monitoring environment in Planning and Development Division, Ministry of Health [compact disc] - 318778 Lornie Enggong (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Sains (Teknologi Maklumat - Pengurusan)) - Universiti Teknologi Malaysia, 2004